Association of the Laterality of Chronic Suppurative Otitis Media with the Laterality of Sinonasal Disease Based on Temporal Bone CT - Scan Results and Lund Mackay Scoring System - Walfrido C. Adan; Emmanuel Tadeus S. Cruz (Philippine Journal of Otolaryngology Head and Neck Surgery, 2016)
Objective: To determine the association between the laterality of chronic suppurative otitis media (CSOM) and the laterality of sinonasal disease, based on temporal bone ct-scan results and Lund-Mackay Scoring system, among patients admitted for ear surgery in a tertiary government hospital in Metro Manila.